Cytogenetic analysis of peripheral blood lymphocytes after arteriography (exposure to x-rays and contrast medium) - Popova, Ljubomira (Radiology and oncology (Ljubljana), 2005)
Backgrounds. The purpose of our study is to investigate the cytogenetic analysis findings in peripheral blood lymphocytes of 29 patients who had undergone diagnostic radiography. Methods. Peripheral blood samples were takenfrom 22 patients submitted to renal arteriography and 7 patients subnutted to cerebral arteriography (17 male and 12 female, aged between 13-68years). Cytogenetic analyses of peripheral lymphocytes were performed before the procedure, immediately after and 24 hours later. The entrance skin dose obtained during the whole diagnostic X-ray exposure was measured by thermoluminescent dosimeters and varied between 0.03-0.30 Gy. Both low and high osmolarity contrast media were used. Chromosomal aberrations and micronuclei frequency were used as biomarkers of genotoxicity. Results. The estimated frequency of chromosomal aberrations and micronuclei in the peripheral blood lymphocytes of patients after arteriography examination was significantly higher than the level before the diagnostic exposure. The mean frequency of cells with chromosomal aberrations was nearly double after examination and proved to be constant in the analysis after 24 hours. Conclusions. Radiological diagnostic procedures involving iodinated contrast media as arteriography may cause a significant increase in cytogenetic damage in peripheral blood lymphocytes.
Keywords: Adverse Effects; Angiografija; Angiography; Chromosome Aberrations; citodiagnostika; diagnostika; Kromosomske aberacije; Limfociti; Lymphocytes; Micronucleus Tests; Mikronukleusni testi; Radiation Effects